The relationship of organic matter, nitrate, and phosphate content to diatom abundance in the eastern coastal waters of Rupat Island Province - Semangat Riski Hasibuan; Bintal Amin; Syahril Nedi (Science, Technology, and Education Care, 2023)
This study was conducted in March 2023 in the coastal waters of the eastern part of the island of Rupat, Riau Province. The method used in this study used the purposive sampling method at 3 station points. Water samples were used to analyze nitrate and phosphate analyzed using Ultraviolet Spectrophotometry, and analysis of water organic matter using the titrimetric method. Diatom sampling using plankton net measuring 25 µm. The results of the study found 14 species from 3 classes of diatoms namely Bacillariophyceae, Cyanophyceae, and Conjugatophyceae. Diatom abundance ranged from 472.22 - 993.05 cells/L. The regression equation for nitrate on diatoms is Y= 929.151-3194.045x. The coefficient of determination (R2) of 0.080 indicates that the effect of nitrate on diatom abundance has a weak close relationship. The effect of phosphate on diatom abundance has a coefficient of determination (R2) of 0.105 and the effect of phosphate has weak proximity. The influence of water organic matter has a coefficient of determination (R2) of 0.033 with a very weak effect. The analysis shows that the concentration of nitrate (NO3) is included in the oligotrophic fertility level, namely the low fertility rate